2019
DOI: 10.21203/rs.2.9643/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Symbiotic bacteria motivate the foraging decision and promote fecundity and survival of Bactrocera dorsalis (Diptera: Tephritidae)

Abstract: Background The gut bacteria of tephritid fruit flies play prominent roles in nutrition, reproduction, maintenance and ecological adaptations of the host. Here, we adopted an approach based on direct observation of symbiotic or axenic flies feeding on dishes seeded with drops of full diet (containing all amino acids) or full diet supplemented with bacteria at similar concentrations to explore the effects of intestinal bacteria on foraging decision and fitness of Bactrocera dorsalis. Results The results show tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Recently, Akami et al . (2019) found that feeding B. dorsalis with Enterobacter cloacae and Pantoea dispersa increased their fecundity and feeding them with Enterococcus faecalis decreased their fecundity, which is similar to our findings that Enterobacter had a positive effect and Enterococcus had a negative impact on the fecundity of Z. tau .…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Akami et al . (2019) found that feeding B. dorsalis with Enterobacter cloacae and Pantoea dispersa increased their fecundity and feeding them with Enterococcus faecalis decreased their fecundity, which is similar to our findings that Enterobacter had a positive effect and Enterococcus had a negative impact on the fecundity of Z. tau .…”
Section: Discussionsupporting
confidence: 90%
“…In tephritid flies, numerous studies have demonstrated that gut bacteria are associated with digestion, detoxification, immune response, metabolism, sexual behavior, reproduction, and survival ( Behar et al, 2005 ; Hosokawa et al, 2007 ; Ben Ami et al, 2010 ; Augustinos et al, 2015 ; Ben-Yosef et al, 2015 ; Akami et al, 2019 ). Various strains of Enterobacteriaceae have been added to artificial larval diets to improve pupal weight and mating performance, and to decrease developmental time, in B. oleae and C. capitata ( Sacchetti et al, 2008 ; Ben Ami et al, 2010 ; Gavriel et al, 2011 ; Hamden et al, 2013 ; Augustinos et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial communities are often highly abundant in insect digestive systems ( Dillon and Dillon, 2004 ), especially bacteria ( Broderick et al, 2004 ; Robinson et al, 2010 ). In many cases, symbiotic bacteria have been found to provide nutrition that contributes to insect host fitness ( Baumann, 2005 ; Akami et al, 2019 ). Microbes can provide amino acids ( Nogge, 1981 ) and essential vitamins ( Douglas, 1998 ), as well as nitrogen and carbon compounds ( Benemann, 1973 ; Dillon and Dillon, 2004 ) to insect hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research also showed that K. michiganensis BD177 improved the mating competitiveness and lifespan of sterile male B. dorsalis [23]. Additionally, the recent study reported that K. oxytoca could affect the foraging decision [52] and mate-selection [53] of B. dorsalis. It is suggested that riboflavin and folate synthetic ability of K. michiganensis BD177 may contribute to the sexual performance and lifespan of B. dorsalis.…”
Section: Discussionmentioning
confidence: 79%